Effect of Adding Bioactive Compounds from Brown Algae (sargassum sp.) in Feed on The Growth Performance of Mahseer Seeds (Tor soro) - M Gufron Sugih; Fittrie Meyllianawaty Pratiwy; Izza Mahdiana; Irfan Zidni (Universitas Islam Lamongan, 2024)
This study aims to determine the influence and determination of the optimal dose of the addition of brown algae extract on the growth performance and immunity of god fish seeds. The research was conducted in March - May 2024, at the Aquaculture Lab Building 4, FPIK Unpad, and the production of brown algae extract was carried out at the Aquaculture Lab Building 2, FPIK Unpad. This study used a complete randomized design (RAL) experimental method with four treatments and four replicates. The treatments given were (A) 100% commercial feed (control), (B) commercial feed added with brown algae extract at a dose of 10gr/kg, (C) commercial feed added with brown algae extract at a dose of 15 g/kg, and (D) commercial feed added with brown algae extract at a dose of 20 g/kg. The maintenance of fish fry is carried out for 40 days, with feeding three times a day. The observed parameters included absolute length growth parameters (L), absolute weight (W), specific growth rate (SGR), feed conversion ratio (FCR), feed utilization efficiency (EPP), and survival rate (SR) which were analyzed using ANOVA (Analysis of Varience) with a confidence level of 95%, if there is a significant difference, followed by the Duncan test. Water quality data was analyzed descriptively. The results showed that the addition of brown algae extract for feed at a dose of 20gr/kg had a more optimal effect than other treatments because of the bioactive compounds it contained. The dose had an effect on the growth of absolute length (1.6 cm), absolute weight (126.3 g), SGR (2.39%), FCR (2.28), EPP (44%) and water quality values during the maintenance period were still in the optimal range for god fish seeds.